The long memory of equity volatility: International evidence - Duc Binh Benno Nguyen; Marcel Prokopczuk; Philipp Sibbertsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper examines long memory volatility in international stock markets. We show that long memory volatility is widespread in eighty-two countries and that the degree of memory can be related to macroeconomic variables such as inflation, unemployment rates, interest rates or stability of a country measured by jumps. The relationships hold both in the time-series and the cross-sectional dimension. We also find that developed countries possess longer memory in volatility than emerging and frontier countries.
Keywords: G15; C22; F30; F40; 330; International; Long Memory; Volatility